(3b2+4)-(8b2-9+b4)

Replace the variable x with -2 in the expression.

f(-2)=-5(-2)2+13-(-2)4

Simplify the result.

Simplify each term.

Raise -2 to the power of 2.

f(-2)=-5⋅4+13-(-2)4

Multiply -5 by 4.

f(-2)=-20+13-(-2)4

Raise -2 to the power of 4.

f(-2)=-20+13-1⋅16

Multiply -1 by 16.

f(-2)=-20+13-16

f(-2)=-20+13-16

Simplify by adding and subtracting.

Add -20 and 13.

f(-2)=-7-16

Subtract 16 from -7.

f(-2)=-23

f(-2)=-23

The final answer is -23.

-23

-23

Convert -23 to decimal.

y=-23

y=-23

Replace the variable x with -1 in the expression.

f(-1)=-5(-1)2+13-(-1)4

Simplify the result.

Simplify each term.

Raise -1 to the power of 2.

f(-1)=-5⋅1+13-(-1)4

Multiply -5 by 1.

f(-1)=-5+13-(-1)4

Multiply -1 by (-1)4 by adding the exponents.

Multiply -1 by (-1)4.

Raise -1 to the power of 1.

f(-1)=-5+13+(-1)(-1)4

Use the power rule aman=am+n to combine exponents.

f(-1)=-5+13+(-1)1+4

f(-1)=-5+13+(-1)1+4

Add 1 and 4.

f(-1)=-5+13+(-1)5

f(-1)=-5+13+(-1)5

Raise -1 to the power of 5.

f(-1)=-5+13-1

f(-1)=-5+13-1

Simplify by adding and subtracting.

Add -5 and 13.

f(-1)=8-1

Subtract 1 from 8.

f(-1)=7

f(-1)=7

The final answer is 7.

7

7

Convert 7 to decimal.

y=7

y=7

Replace the variable x with 0 in the expression.

f(0)=-5(0)2+13-(0)4

Simplify the result.

Simplify each term.

Raising 0 to any positive power yields 0.

f(0)=-5⋅0+13-(0)4

Multiply -5 by 0.

f(0)=0+13-(0)4

Raising 0 to any positive power yields 0.

f(0)=0+13-0

Multiply -1 by 0.

f(0)=0+13+0

f(0)=0+13+0

Simplify by adding zeros.

Add 0 and 13.

f(0)=13+0

Add 13 and 0.

f(0)=13

f(0)=13

The final answer is 13.

13

13

Convert 13 to decimal.

y=13

y=13

Replace the variable x with 1 in the expression.

f(1)=-5(1)2+13-(1)4

Simplify the result.

Simplify each term.

One to any power is one.

f(1)=-5⋅1+13-(1)4

Multiply -5 by 1.

f(1)=-5+13-(1)4

One to any power is one.

f(1)=-5+13-1⋅1

Multiply -1 by 1.

f(1)=-5+13-1

f(1)=-5+13-1

Simplify by adding and subtracting.

Add -5 and 13.

f(1)=8-1

Subtract 1 from 8.

f(1)=7

f(1)=7

The final answer is 7.

7

7

Convert 7 to decimal.

y=7

y=7

Replace the variable x with 2 in the expression.

f(2)=-5(2)2+13-(2)4

Simplify the result.

Simplify each term.

Raise 2 to the power of 2.

f(2)=-5⋅4+13-(2)4

Multiply -5 by 4.

f(2)=-20+13-(2)4

Raise 2 to the power of 4.

f(2)=-20+13-1⋅16

Multiply -1 by 16.

f(2)=-20+13-16

f(2)=-20+13-16

Simplify by adding and subtracting.

Add -20 and 13.

f(2)=-7-16

Subtract 16 from -7.

f(2)=-23

f(2)=-23

The final answer is -23.

-23

-23

Convert -23 to decimal.

y=-23

y=-23

The 4th degree function can be graphed using the function behavior and the points.

xy-2-23-17013172-23

The 4th degree function can be graphed using the function behavior and the selected points.

Falls to the left and falls to the right

xy-2-23-17013172-23

Graph (3b^2+4)-(8b^2-9+b^4)